(untitled) (American Journal of Humanities and Social Sciences, 2013)
<!–[if gte mso 9]> <![endif]–> This study examines how strengthening the Small and Medium Enterprises (SMEs) contributes to poverty reduction in north western Nigeria. Primary data was collected through the administration of Questionnaire from a sample of 400 SMEs in Sokoto and Zamfara states that sought information on their main features and the manner of their operations. Also secondary information was obtained from publications of the Nigerian Stock Exchange (NSE) and National Bureau of Statistics (NBS) to look at the performance of the listed companies (large corporations) and both intra and inter-sectorial comparisons of the two sets of enterprises were made with regards to their employment generation and utilization of indigenous technology. T-test analysis was used in analyzing the information obtained. The major findings of the study is that large enterprises contribute more in the area of employment provision than the SMEs going by the country – wide data. This contradicts the a priori assumption that small and medium enterprises do contribute to employment generation and use more indigenous technology than large corporations, The study concludes that employment generation capacities of any organization is vital in reducing the incidence of poverty among economic agents. A major recommendation of the study is that government should make a practical approach to poverty alleviation by emphasizing on the strength of the poor and their productive capacity and not on their weaknesses. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>